A systematic review of hot weather impacts on infant feeding practices in low-and middle-income countries - Edney, Jessica M.; Kovats, Sari; Filippi, Veronique; Nakstad, Britt (Frontiers in Pediatrics, 2022)
Background: Increased rates of exclusive breastfeeding could significantly improve infant survival in low- and middle-income countries. There is a concern that increased hot weather due to climate change may increase rates of supplemental feeding due to infants requiring fluids, or the perception that infants are dehydrated. Objective: To identify and appraise evidence that exclusively breastfed infants can maintain hydration under hot weather conditions in the first six months of life in low- and middle-income settings. To identify and appraise research investigating infant feeding practices during episodes of hot weather or during the hot season. Methods: Systematic review of published studies that met inclusion criteria in MEDLINE, EMBASE, Global Health and Web of Science databases. The quality of included studies was appraised against predetermined criteria and relevant data extracted to produce a narrative synthesis of results. Results: Eighteen studies were identified. There is no evidence among studies of infant hydration that infants under the age of six months require supplementary food or fluids in hot weather conditions. In some settings, healthcare providers and relatives continue to advise water supplementation in hot weather or during the warm seasons. Cultural practices, socio-economic status, and other locally specific factors also affect infant feeding practices and may be affected by weather and seasonal changes themselves. Conclusions: Interventions to discourage water/other fluid supplementation in breastfeeding infants below six months are needed, especially in low-middle income countries. Families and healthcare providers should be advised that EBF is recommended even in hot conditions.